A volterra series model for the system level simulation of a wide range of wireless RF blocks - Lavrador, P.M.
This paper discusses the applicability of an orthogonally extracted Volterra series behavioural model to the system level simulation of a wide range of RF blocks. Two reference circuits were used in a simulator as test systems for model extraction and validation: a nonlinear system with linear memory (Hammerstein system) and a nonlinear system with nonlinear memory (feedback system) [1]. Using these system level blocks, we were able to vary both their nonlinearity and memory effects and show how the proposed model keeps its accuracy even when validated under a different signal excitation and varying power level. © 2010 IEEE.